A hetero-phase growth method to control the crystal growth of β-antimony single crystals with high quality and large sizes. Issue 37 (1st September 2022) - Zhao, Xuewen; Xu, Xuequan; Zhao, Rongzheng; Gu, Mengyue; Yang, Na; Huang, Lei; Fu, Chengcheng; Cheng, Yonghong; Zhang, Jinying
Abstract : A hetero-phase crystal growth method was proposed by introducing a heteroelement to yield large antimony single crystals with high quality. Abstract : Large single crystals of high quality are essential for studying the fundamental physical properties of materials and their further applications. However, it is always a big challenge to grow high-quality large single crystals. Increasing the crystal growth time and feedstock is an effective path to increase the crystal size and quality. A heteroelement was introduced to increase the crystal growth temperature range and feedstock to yield high-quality large single crystals in this study. Phosphorus was introduced to produce the P–Sb–Sn–I vapor phase at temperatures above 550 °C, and the Sb source for the crystal growth was significantly increased compared to the Sb–Sn–I vapor phase without phosphorus. The nucleation temperature of Sb was also significantly increased to extend the crystal growth temperature range due to the increased concentration of Sb as a result of the separation out of phosphorus from the P–Sb–Sn–I vapor phase to grow violet phosphorus at a temperature under 530 °C. High-quality β-antimony single crystals with a size of almost a centimeter have then been successfully synthesized using the hetero-phase growth method. The lattice structure of β-antimony single crystals has been obtained by single-crystal x-ray diffraction to be trigonal with a space group of R 3̄ m . Sharp (003) and (006) peaks with full width at half maximum of 0.063° and 0.060° have been detected from the X-ray rocking curve of the as-produced β-antimony single crystals, indicating a low dislocation density and residual stress in the crystals. The hetero-phase growth method has been demonstrated to be an effective path to yield high-quality large antimony single crystals, which can also be adopted to produce other high-quality large single crystals.